Implementation of a nutrition screening tool to improve nutritional status of children with cancer in Singapore's largest paediatric hospital. Issue 1 (11th March 2021) - Han, Wee Meng; Koo, Jasly YS; Lim, Yan Yin; Iyer, Prasad; Ong, Chengsi; Tong, Jasper WK; Chan, Mei Yoke
Abstract : Poor nutritional status in children with cancer can impact treatment outcomes and mortality. Nutrition screening is a simple yet effective approach to identify malnutrition risk for early intervention. We aim to improve the identification of children with cancer at high risk of malnutrition, so that nutritional intervention and rehabilitation can commence early for these children. Our multidisciplinary team conducted a root cause analysis and concluded that the generic screening tool did not differentiate malnutrition risk for different cancer types, stage and intensity of treatment. Hence, a screening tool that considered the identified factors was tested for reliability and validity first. Subsequently, we used the Plan, Do, Study, Act model with two improvement cycles to put in place a systematic process to facilitate the implementation. The interventions included (1) instituting the tool in the electronic medical records and (2) direct referral to dietitian based on screening score. We compared pre- and post-implementation cohorts and demonstrated better identification of nutritionally at-risk patients (36.4%–85.7%, p<0.001) with the new tool as well as improved timeliness of nutritional intervention (3 days to 1 day from admission, p=0.010). A lower malnutrition rate (17.4%–6.5%, p<0.001) in the postimplementation cohort was also demonstrated. Nutritional intervention within 48 hours of admission led to an overall positive weight change at 3 months (+2.68%, IQR: −1.14 to 9.09 vs −0.43%, −6.60 to 2.29; p=0.036) in the malnourished patients from both cohorts. Further studies will be conducted to evaluate the scale of the effectiveness of early intervention and close nutritional monitoring, in improving the nutritional status of children with cancer. The collaborative partnership among the doctors, nurses and dietitians has helped to streamline and simplify nutrition screening, making it an efficient and sustainable system in our hospital.